MODERN STRATEGIES FOR MANAGING ARTERIAL HYPERTENSION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Каширина, Евгения Петровна; Маклакова, Татьяна Петровна; Каширина, Елена Жоржевна; Рыженкова, Евгения Михайловна (Medicine in Kuzbass, 2024)
The Type 2 Diabetes is a pandemic of cardio-renal complications causing premature death in patients. The high incidence of cardiovascular diseases in diabetes is due to a combination of specific and general population risk factors, the most significant of which are arterial hypertension, dyslipidemia, obesity, low physical activity. Arterial hypertension is detected in 60-80 % of patients with type 2 diabetes; when combined, the risk of cardiovascular diseases increases by 75 %, which increases overall morbidity and mortality The purpose of the publication is to attract the attention of primary care physicians to the most significant controllable cardiovascular risk factors, modern strategies for the diagnosis and treatment of arterial hypertension in type 2 diabetes mellitus. The characteristics of the main classes of antihypertensive drugs, their rationale for use in patients with diabetes mellitus, and step-by-step intensification of therapy are presented.
Keywords: diabetes mellitus type 2; arterial hypertension; cardiovascular risks; classes of antihypertensive drugs; treatment strategy